Respuesta :
Answer:
5x + 2
Step-by-step explanation:
Given
10x² - 11x - 6
Consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term.
product = 10 × - 6 = - 60 and sum = - 11
The factors are - 15 and + 4
Use these factors to split the x- term
10x² - 15x + 4x - 6 ( factor the first/second and third/fourth terms )
= 5x(2x - 3) + 2(2x - 3) ← factor out (2x - 3) from each term
= (x - 3)(5x + 2) ← in factored form
Thus 5x + 2 is a factor of 10x² - 11x - 6